2016
DOI: 10.3390/molecules21040454
|View full text |Cite
|
Sign up to set email alerts
|

Wild Bitter Melon Leaf Extract Inhibits Porphyromonas gingivalis-Induced Inflammation: Identification of Active Compounds through Bioassay-Guided Isolation

Abstract: Porphyromonas gingivalis has been identified as one of the major periodontal pathogens. Activity-directed fractionation and purification processes were employed to identify the anti-inflammatory active compounds using heat-killed P. gingivalis-stimulated human monocytic THP-1 cells in vitro. Five major fractions were collected from the ethanol/ethyl acetate extract of wild bitter melon (Momordica charantia Linn. var. abbreviata Ser.) leaves and evaluated for their anti-inflammatory activity against P. gingival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 45 publications
1
34
0
Order By: Relevance
“…This activity was attributed to the anti-inflammatory effects of phenolic compounds present in the extract (Huang et al, 2015). Cucurbitane triterpenods isolated from MC leaves strongly suppressed Porphyromonas gingivalis -induced IL-8, IL-6, and IL-1β levels (Tsai et al, 2016).…”
Section: Anti-inflammatory and Anti-oxidant Activity Of Momordica Chamentioning
confidence: 99%
“…This activity was attributed to the anti-inflammatory effects of phenolic compounds present in the extract (Huang et al, 2015). Cucurbitane triterpenods isolated from MC leaves strongly suppressed Porphyromonas gingivalis -induced IL-8, IL-6, and IL-1β levels (Tsai et al, 2016).…”
Section: Anti-inflammatory and Anti-oxidant Activity Of Momordica Chamentioning
confidence: 99%
“…Abundant evidences showed that Traditional Chinese Medicine (TCM) can present the progression of atherosclerosis via anti-oxidation and anti-inflammation [ 3 5 ]. The bioactive components of bitter melon, one of the most common TCMs, have been reported to improve the glucose and lipids metabolism, important risk factors of atherosclerosis, via anti-oxidation and anti-inflammation [ 6 9 ]. Furthermore, studies show that BM can regulate metabolism through the activation of peroxisome proliferator-activated receptor (PPAR) and AMP-activated protein kinase (AMPK) [ 10 16 ], which may represent protective mechanisms against atherosclerosis via potential anti-inflammation in endothelial cells [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cucurbitane triterpenods previously isolated from leaves of wild M. charantia potently suppressed Porphyromonas gingivalisinduced IL-8, IL-6, and IL-1␤ levels (Tsai et al, 2016). Methanolic extract of M. charantia leaves inhibited the carrageenan-induced edema in vivo with results comparable to indomethacin (Ganesan et al, 2008).…”
Section: Anti-inflammatory Activitymentioning
confidence: 77%